Evaluation of Unowned Domestic Cat Management in the Urban Environment of Rome After 30 Years of Implementation of the No-Kill Policy (National and Regional Laws) - Natoli, Eugenia; Malandrucco, Livia; Minati, Laura; Verzichi, Stefania; Perino, Raffaella; Longo, Laura; Pontecorvo, Francesca; Faini, Anna (Frontiers in Veterinary Science, 2019)
Law no. 281, enacted by the Italian Parliament in 1991, was the first that aimed at managing urban free-roaming cats living in colonies, without killing and/or moving them from their site. It had been anticipated by the Lazio Regional Law no. 63/1988 and subsequently refined by the Lazio Regional Law no. 34/1997. These laws introduced: i) the cats’ right to live free and safe; ii) the compulsory neutering of cats by the Veterinary Services of the Local Health Unit; iii) the institutionalization of cat caretakers. Within this context, this paper intends to evaluate the effects of the application of the Italian laws on management of urban free-roaming cats for the years 1988 to 2018. To this end, some indicators have been built and applied to our activity data: number of censused colonies and number of cats; number of stable colonies due to neutering; number of hygiene and sanitary notifications; number of notifications to check cat welfare; number of bites by unowned free-roaming cats; number of notifications of cat poisoning. The number of citizens’ requests for institutional interventions by public veterinary services in cat colonies management and, accordingly, the detection of cat colonies yet unknown, seem to confirm the interest of people to control the cat colonies in Rome in an humanitarian way, as evidenced in our data. This fact/phenomenon should be analysed in its multiple dimensions, also including the many changes and social unrests which have affected the human-cat relationship in the last thirty years.